2015
DOI: 10.1021/acs.bioconjchem.5b00144
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Binding Affinities for Nanoparticles Targeted to Vulnerable Plaque

Abstract: Recent successes in targeted immune and cell-based therapies have driven new directions for pharmaceutical research. With the rise of these new therapies there is an unfilled need for companion diagnostics to assess patients’ potential for therapeutic response. Targeted nanomaterials have been widely investigated to fill this niche; however, in contrast to small molecule or peptide-based targeted agents, binding affinities are not reported for nanomaterials, and to date there has been no standard, quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The synthesis and physical characterization of both DIO and SDIO were reported in a previous article [ 30 ]. The properties of the materials synthesized for the current studies were confirmed to match to our published results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The synthesis and physical characterization of both DIO and SDIO were reported in a previous article [ 30 ]. The properties of the materials synthesized for the current studies were confirmed to match to our published results.…”
Section: Resultsmentioning
confidence: 99%
“…dextran sulfate) is widely known as one of the ligands for SR-A with a K d of 3 nM [ 29 ]. In our previous study, we have confirmed that the sulfation of dextran coating significantly improved the cellular binding and uptake of these nanoparticles by macrophages and the uptake efficiency enhances with higher level of surface sulfation [ 30 ]. The sulfated dextran-coated iron oxide nanoparticles have a similar binding affinity to the SR-A, compared with dextran sulfate itself.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations